CASE STUDY ON THE MANAGEMENT OF ELDERLY PATIENTS WITH GERIATRIC ANOREXIA ACCOMPANIED BY DECUBITUS ULCERS AND A HISTORY OF STROKE IN A BATANG DISTRICT HOSPITAL: A CLINICAL APPROACH AND MANAGEMENT WITH A LITERATURE REVIEW - Muhammad Hikmawan Priyanto; Ibnu Mas’ud (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
ABSTRACT BACKGROUND Anorexia of Aging (AA) refers to the loss of appetite in the elderly caused by the aging process. Geriatric anorexia is a common syndrome that includes loss of appetite and related disorders, with serious impacts and increasing prevalence in the global elderly population. Many risk factors for geriatric anorexia can be modified through early detection and appropriate intervention, making it important not to consider it an inevitable condition in the aging process. CASE PRESENTATION A 72-year-old male presented to the emergency department with the main complaints of weakness for one week, refusal to eat and drink, and painful wounds in the mid-lumbar region. The working diagnosis for the patient was geriatric anorexia, decubitus ulcer in the sacral region, and a history of chronic cardiovascular disease (CVD). The patient was treated by an internist for his geriatric anorexia, referred to a surgeon for excisional debridement, and referred to a rehabilitation physician for infrared therapy, general passive range of motion (ROM), and mobilization. Other therapies included nursing care such as pain management, wound care, and nutritional care in the form of a soft low-carbohydrate diet. After 7 days, the patient was discharged with clinical improvement and education on follow-up care at home. DISCUSSION This case involves an elderly male with weakness, loss of appetite, and a diminished sense of taste for one week, as well as increasingly painful wounds in the lumbar region. The patient, who had a stroke three years ago, had been lying on a mattress and had a BMI of 17.9 (underweight). The causes of anorexia in the elderly are not fully understood but may involve hormonal changes, medication use, and social conditions. Early detection and prevention of anorexia are crucial to reduce morbidity and mortality, with screening tools such as the SNAQ that can be helpful. The patient was treated by an internist with infusion therapy, injections, and a regular diet. Consultation with a surgeon was conducted to address the infection, and nursing care included monitoring vital signs, pain management, and activity motivation. A nutritionist provided a soft diet, and a rehabilitation physician conducted therapy and family education. Guidelines for managing anorexia in the elderly include food manipulation, assistance during meals, and socialization. Research on non-pharmacological interventions is still limited, and the role of caregivers is essential in recognizing and implementing care plans. This case demonstrates that geriatric anorexia, often starting from anorexia of aging, requires comprehensive intervention to prevent worsening conditions. Unfortunately, the patient could not be followed up in outpatient services. CONCLUSION Anorexia in the elderly is a geriatric syndrome caused by illness, medication side effects, or aging, resulting in decreased food intake, weight loss, and muscle mass, as well as increased risk of weakness. Management involves identifying risk factors, screening, and prompt intervention. In this case, anorexia was confirmed through SNAQ in a patient with stroke, decubitus ulcer infection, and weakness. Management requires intraprofessional collaboration to treat infections and prevent malnutrition.